Development And Validation of A Customer Relationship Scale For Airline Companies - Gisela Demo; Kesia Rozzett; Natasha Fogaça; Taila Souza (BBR: Brazilian Business Review)
Businesses with focus on customers through the use of Customer Relationship Management (CRM) perform better and win customer loyalty. Therefore, it is relevant to study the relationship between customers and airline companies, given that the aviation industry is highly competitive and relatively commoditized. Thus the aim of this study was to develop and validate a scale to measure customer’s perception of relationship with airline companies. The scale was composed of four primary factors (customer loyalty, purchase experience, flight experience, and service) and a second order factor (customer relationship), all with good psychometric indices. The development and validation of a scale in an industry little explored by the CRM literature was the main contribution of this research, as it may be used as a diagnostic tool for airline companies to scale up their relationship with strategic customers and achieve more effective results.